Synthesis and characterization of gold nanoparticles from Abies spectabilis extract and its anticancer activity on bladder cancer T24 cells. Issue 1 (4th December 2019) - Wu, Tao; Duan, Xi; Hu, Chunyan; Wu, Changqiang; Chen, Xiaobin; Huang, Jing; Liu, Junbo; Cui, Shu
Abstract: In recent times, Gold nanoparticles (AuNPs) synthesized from plant extracts and their anticancer activity have attracted significant attention. We report the green approach for the synthesis of AuNPs using extract from Abies spectabilis plant. In this study, the reaction parameters were optimized to control the size of the nanoparticle, which was confirmed by Transmission Electron microscopy (TEM). Various characterization technique such as SAED pattern, UV visible spectroscopy, EDX, FTIR, and AFM were employed to analyze the synthesized AuNPs obtained from A. spectabilis plant extract. Furthermore, we investigated the anticancer activities using T24 cell lines. Interestingly, the results of extensive screening on the applications of newly synthesized AuNPs were tested for their cytotoxicity effects on anticancer activity against T24 cells by MTT assay. The cell apoptosis was studied using TUNEL, DAPI, caspase activity, cell invasion and migration. Nanoparticles at different concentrations ranging from 1 to 25 μg/ml exhibited a dose dependent cytotoxicity for 24 h. Condensation and DNA fragmentation are characteristic of apoptosis by DAPI, TUNEL staining, and the significant up regulations of Beclin-1, Bax and caspase 3, whereas the expressions of anti-apoptotic Bcl-2 and Bid were down regulated. However, this study, therefore attempts to report the synthesis, characterization, and anticancer activity of gold nanoparticles of A. spectabilis plant extract beneficial for cancer therapeutics.